Free-living microturbellarians (Platyhelminthes) from wetlands in Southern Brazil, with the description of three new species - Reyes Pajuelo, Jhoe Steve (2021)
The Taim strict nature reserve (ESEC Taim) is a protected wetland (Ramsar site) in southern Brazil. Although the ESEC Taim harbours a broad conspicuous flora and fauna, this area lacks studies on free-living Platyhelminthes. Here, we describe three new species to science, one belonging to Macrostomorpha (Macrostomum itai n. sp.) and two belonging to Dalytyphloplanoida (Gieysztoria duopunctata n. sp. and G. hermes n. sp.). Macrostomum itai n. sp. differs from their congeners for its distinct stylet in “J”-shaped. Gieysztoria duopunctata n. sp. is distinguishable based on the crown-like penis stylet, this species possesses 12–18 spines of similar sizes and two smaller spines (one a bit longer than the other). Gieysztoria hermes n. sp. clearly differs from its congeners owing to its fibrous girdle, which bears two groups of complexes of spines and three different-in-length ventral spines. Moreover, we identified twenty-three species, eleven belonging to Catenulida, three to Macrostomorpha, seven to Dalytyphloplanoida, one to Kalyptorhynchia, and one to Prorhynchida. We recorded three species for the first time in Brazil (Myostenostomum vanderlandi, Macrostomum quiritium and Strongylostoma elongatum). This new information on these free-living Platyhelminthes makes this protected area a more valuable and reinforces the actions that are being done to protect it.